Lugar incerto: o endereço como infraestrutura urbana e social - Urnhani, Rafael (2021)
The term uncertain place appears frequently in notifications of legal acts when it is not possible to determine the exact address of a defendant, and can roughly designate unidentified areas in municipal records, as is the case with informal settlements. In practice, the lack of an address compromises inspection, monitoring, maintenance and taxation actions by the government, and makes it difficult for the population to exercise certain civil and contractual rights, such as access to the public health and education systems. In this context, this bibliographic research evaluates the dysfunctions caused by the lack of an address and the link between informality and the uncertain places, making the formal address an important instrument of technical, administrative and social dimension, capable of articulating basic levels of citizenship.